RELIGIOUS AFFILIATION AS AN INDICATOR OF NATIONAL IDENTITY: (The case of religious minorities in Bessarabia) (Philological Studies, 2019)
This paper addresses the correlation between ethnicity and confessional identity existing in different communities of Bessarabia in the 19th century. Historiography and data from archive documents show that a number of ethno-confessional communities can be found on the studied diachronic segment of the Prut-Nistru territory, where the ethnic and religious affiliation constituted one whole, while both components constituting to the same extent elements that used to determine the affiliation to one or other community. In this case, we refer to Armenian, Romano-Catholic, and Protestant communities or to a number of religious denominations.